Special paperEndovascular approaches for acute ischaemic stroke: the current evidence and organizational issues - Kobayashi, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Stroke is a leading cause of death and the most frequent cause of disability in adults. The specific evidence-based treatments include intravenous thrombolysis, aspirin and stroke unit care. They are associated with a reduction in mortality and increase in the chance of being independent. Endovascular approaches have been emerging as a new option in the management of stroke. They are associated with a higher recanalization rate of intracranial arteries. Several smaller trials have shown that intra-arterial thrombolysis with pro-urokinase can be effective in acute stroke with large artery occlusion, but the drug has been withdrawn from the market. Currently recombinant tissue plasminogen activator (rt-PA) is most widely used for this purpose. Mechanical thrombectomy is a very promising new method with a high recanalization rate. Still its efficacy has not been proven in the settings of randomized controlled trials, which are currently under way. There are several devices commercially available that have been introduced and some of them already approved for use by regulatory authorities. The most frequently used are the MERCI, Penumbra and Solitaire FR devices. The procedures should be performed in a setting of a comprehensive stroke unit. There is an urgent need for creating training systems in neuroendovascular medicine in Europe similar to the American system to provide appropriate care. There is also a great need for randomized clinical trials which will confirm the efficacy of the endovascular strategies for ischaemic stroke.